Distance-to-Default in Banking : A Bridge Too Far? - Sy, Amadou (IMF Working Papers; Working Paper ;, 2006)
In contrast to corporate defaults, regulators typically take a number of statutory actions to avoid the large fiscal costs associated with bank defaults. The distance-to-default, a widely used market-based measure of corporate default risk, ignores such regulatory actions. To overcome this limitation, this paper introduces the concept of distance-to-capital that accounts for pre-default regulatory actions such as those in a prompt-corrective-actions framework. We show that both risk measures can be analyzed using the same theoretical framework but differ depending on the level of capital adequacy thresholds and asset volatility. We also use the framework to illustrate pre-default regulatory actions in Japan in 2001-03.